2012
DOI: 10.1007/s00253-012-4616-9
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies distances between propionic acid degraders and methanogens in syntrophic consortia for optimal hydrogen transfer

Abstract: A mixed culture from an anaerobic biowaste digester was enriched on propionate and used to investigate interspecies hydrogen transfer in dependence of spatial distances between propionate degraders and methanogens. From 20.3 mM propionate, 20.8 mM acetate and 15.5 mM methane were formed. Maximum specific propionate oxidation and methane formation rates were 49 and 23 mmol mg(-1) day(-1), respectively. Propionate oxidation was inhibited by only 20 mM acetate by about 50 %. Intermediate formate formation during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 54 publications
2
21
0
2
Order By: Relevance
“…Previous studies reported that the syntrophic coculture of a propionate degrader and a hydrogenotrophic methanogen could form cell aggregates while growing on propionate for optimal hydrogen transfer (27,56). A similar phenomenon was also observed in mixed cultures containing propionate degraders and methanogens enriched from an anaerobic biowaste digester where flocs formed showing that reducing the interspecies distances by aggregation was advantageous in complex ecosystems (57). In engineered dechlorinating systems, D. mccartyi species have been observed in biofilms within a membrane bioreactor (58) and in bioflocs maintained in a continuous flow bioreactor fed with butyrate (13).…”
Section: Discussionmentioning
confidence: 48%
“…Previous studies reported that the syntrophic coculture of a propionate degrader and a hydrogenotrophic methanogen could form cell aggregates while growing on propionate for optimal hydrogen transfer (27,56). A similar phenomenon was also observed in mixed cultures containing propionate degraders and methanogens enriched from an anaerobic biowaste digester where flocs formed showing that reducing the interspecies distances by aggregation was advantageous in complex ecosystems (57). In engineered dechlorinating systems, D. mccartyi species have been observed in biofilms within a membrane bioreactor (58) and in bioflocs maintained in a continuous flow bioreactor fed with butyrate (13).…”
Section: Discussionmentioning
confidence: 48%
“…Recently, Felchner-Zwirello et al (2013) measured interbacterial distances between the propionate degraders and methanogens in syntrophic associations within granules that increased in size with time after inoculation of the growth media. According to these authors, the two microbial types find each other (probably by quorum sensing) and the aggregates increase in size over time, while the interspecies distances decrease from 5.30 to 0.29 mm.…”
Section: Formate In Interspecies H 2 Transfermentioning
confidence: 99%
“…Felchner-Zwirello et al [29] even observed that the interbacterial distances between propionate degraders and methanogens decreased from 5.30 to 0.29 μm when these microorganisms formed aggregates of up to 54 μm, causing an increase of the maximum possible H 2 flux from 1.1 to 10.3 nmol ml À 1 min À 1 . Therefore, reducing the interspecies distance by aggregation is supposedly advantageous in complex methanogenic system.…”
Section: Methanogenic Aggregatesmentioning
confidence: 99%
“…Besides, the formation of granules is advantageous for interspecies H 2 transfer. In granules, microbes are densely packed together, and the small distance between cells facilitates H 2 diffusion [29]. Intact granules display high methanogenic activities with fatty acids as substrates.…”
Section: Interspecies H 2 Transfer In Bioreactorsmentioning
confidence: 99%
See 1 more Smart Citation